2004
DOI: 10.1017/s0317167100003723
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rates in Standard vs. Hydrogel Coated Ventricular Catheters

Abstract: Background:Infection related to external ventricular drain (EVD) use is a common neurosurgical complication. Modified catheters with a hydrophilic surface may impede bacterial adherence and thereby reduce catheter related cerebrospinal fluid (CSF) infection.Methods:A prospective randomized clinical trial compared the occurrence of CSF infection related to use of either standard silastic or hydrogel coated EVD catheters (Bioglide®, Medtronic). Enrolment was available to all adult neurosurgery patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Chemiluminescence demonstrated that HCCs significantly reduced adhesion of S. epidermidis. A Canadian group conducted a prospective randomized clinical trial to compare the occurrence of CSF infection with use of either standard silastic or hydrogel coated EVD catheters [36]. The authors studied 158 adult neurosurgery patients at three university centers who were undergoing placement of a first EVD.…”
Section: Antibiotic-coated External Ventricular Drains: In Vitro Datamentioning
confidence: 99%
“…Chemiluminescence demonstrated that HCCs significantly reduced adhesion of S. epidermidis. A Canadian group conducted a prospective randomized clinical trial to compare the occurrence of CSF infection with use of either standard silastic or hydrogel coated EVD catheters [36]. The authors studied 158 adult neurosurgery patients at three university centers who were undergoing placement of a first EVD.…”
Section: Antibiotic-coated External Ventricular Drains: In Vitro Datamentioning
confidence: 99%
“…Our study has found a significant incidence of VPS-related CSF infections with coincidence of previous researches. [3033] According to our experience, the infection rates in normal patients are much lower but can still cause serious consequences if infection occurs. Because the catheter is not the organic part of the body, the infection is more likely to occur compared with regular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that it may contribute to a reduced infection rate [2932] whereas others have reported little benefits. [3335] According to our assumption, the infecting bacteria enter the intracranial system at the point of catheter insertion and develop at a favorable catheter spot with little immunological intervention within the central nerve system. Nevertheless, the shunt devices can absorb antibiotics during the presoaking period and lower the shunt infection rate which is supported by various recent reports.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were controversial depending on the coating material used. One RCT did not show any benefit with the use of hydrogel-coated catheters presoaked in bacitracin solution (Kaufmann, et al, 2004). Silver-coated catheters were first used in central venous line with equivocal results (Bach, et al, 1999;Kalfon, et al, 2007).…”
Section: Coated Ventricular Cathetermentioning
confidence: 99%